Pomalidomide in Patients With Relapsed and/or Refractory Multiple Myeloma: A Prospective Study Within the Nationwide Netherlands Cancer Registry. Issue 2 (27th February 2022) - Wester, Ruth; Dinmohamed, Avinash G.; van der Holt, Bronno; Zweegman, Sonja; Minnema, Monique; Croockewit, Sandra; Levin, Mark-David; Libourel, Eduard; de Waal, Esther; Sonneveld, Pieter; Cornelissen, Jan; Blijlevens, Nicole; et al.
Abstract : Patients with relapsed and/or refractory multiple myeloma (RRMM) generally have limited treatment options and a poor prognosis. Previous trials demonstrated that pomalidomide combined with low-dose dexamethasone (Pd) is effective in these patients with significant responses and improved progression-free survival (PFS). Pd has been approved in RRMM patients who received ≥2 prior lines of therapy. Here, we present the results of a population-based study of patients with RRMM treated with Pd in The Netherlands from time of pomalidomide approval. Using the nationwide Netherlands Cancer Registry, data from all nontrial patients with RRMM treated with Pd were collected. Data were analyzed of response, PFS, and overall survival (OS). A total of 237 patients were included in this analysis. Previous treatment consisted of a proteasome inhibitor in 227 patients (96%) and/or an immune-modulating agent in 235 patients (99%). One hundred forty patients (59%) were refractory to an immune-modulating agent in their last line of therapy. Median time from diagnosis to treatment with Pd was 4.9 years (interquartile range, 2.7–7.9), and the median number of prior treatments was 4 (interquartile range, 3–5). Median PFS and OS for all patients were 3.6 months (95% confidence interval [CI], 3.1–3.8) and 7.7 months (95% CI, 5.7–9.7), respectively. For patients achieving ≥PR, median PFS and OS were 10.6 months (95% CI, 8.3–12.9) and 16.3 months (95% CI, 13.6–23.2), respectively. This nationwide, population-based registry study confirms data shown in pivotal clinical trials on Pd. PFS in this analysis is comparable to PFS observed in those clinical trials.